Forms of special knowledge used during the investigation of secret theft of someone else's property - O. V. Haidar (Law and Safety)
The concept of special knowledge forms used during pre-trial investigation is considered. The views of scientists regarding the classification of special knowledge forms used during the investigation of criminal proceedings are analyzed. The opinion of the majority of scientists regarding the division of forms of special knowledge into procedural and non-procedural ones is highlighted. In addition, besides procedural and non-procedural forms of special knowledge, the statement on the selection of such a form as mixed, which combines the features of the two forms indicated above, is considered. Another division of special knowledge by forms is also analyzed. Each form of special knowledge is explored in more detail.